2021
DOI: 10.1002/adfm.202101554
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Thermoelectric Performance in Environmentally Friendly SnTe Achieved through Stress‐Induced Lotus‐Seedpod‐Like Grain Boundaries

Abstract: In an effort to improve the thermoelectric performance of the environmentally friendly SnTe, here, a multilevel structure composed of “lotus‐seedpod‐like” grain boundaries, dense dislocations, and nanopores is innovatively constructed, which synergistically reduces the sound velocity and the phonon relaxation time, resulting in ultralow lattice thermal conductivity throughout a wide temperature range. An ultrahigh figure of merit, ZT, of ≈1.7 and an unprecedented average ZT of ≈1 from 300 to 873 K are obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 52 publications
(29 reference statements)
1
34
0
Order By: Relevance
“…A peak ZT of 1.66 and 1.31 at 800 K is predicted for p- and n-type materials, respectively, when the lattice thermal conductivity (κ lattice ) is 0.4 Wm –1 K –1 . By implementing ways to reduce κ lattice during the synthesis, one can really develop a promising p- and n-type material by regulating the carrier concentration by controlling the vacancies . Methods like self-compensation to tune the vacancies followed by vanadium doping is believed to result in a promising thermoelectric material. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A peak ZT of 1.66 and 1.31 at 800 K is predicted for p- and n-type materials, respectively, when the lattice thermal conductivity (κ lattice ) is 0.4 Wm –1 K –1 . By implementing ways to reduce κ lattice during the synthesis, one can really develop a promising p- and n-type material by regulating the carrier concentration by controlling the vacancies . Methods like self-compensation to tune the vacancies followed by vanadium doping is believed to result in a promising thermoelectric material. ,, …”
Section: Resultsmentioning
confidence: 99%
“…32 By implementing ways to reduce κ lattice during the synthesis, one can really develop a promising p-and n-type material by regulating the carrier concentration by controlling the vacancies. 46 Methods like selfcompensation to tune the vacancies followed by vanadium doping is believed to result in a promising thermoelectric material. 6,24,47 ■ CONCLUSIONS This work reports vanadium as a resonant dopant in SnTe for the first time, adding a second candidate to n-type resonant dopants in the SnTe family.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…SnTe, a rock salt analogue of PbTe has been receiving increasing attention due to its tunable crystal and electronic structure. [1][2][3][4] Pristine SnTe is considered as a poor thermoelectric due to large number of inherent vacancies, low band gap and high energy offset between its conduction and valence sub-bands which results in poor power factor. Also, SnTe possess high thermal conductivity further reducing the figure of merit, ZT value.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has confirmed that such a pore structure can decrease the sound velocity and phonon relaxation time, therefore reducing the κ l without sacrificing the electrical transport properties, which is beneficial to the TE performance. 45 A typical high-angle annular dark-field (HAADF) TEM image (Figure 2e) of SnTe−Sb 0.06 shows darker Z-contrast at grain boundaries, indicating the existence of enriched nanosized secondary phases with a smaller average atomic number than the SnTe matrix. Furthermore, the corresponding element maps shown in Figure 2f−h suggest the distribution of the Sn, Te, and Sb elements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%